2008
DOI: 10.1111/j.1742-4658.2008.06389.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel bradykinin potentiating peptide isolated from Bothrops jararacussu venom using catallytically inactive oligopeptidase EP24.15

Abstract: Characterization of the peptide content of venoms has a number of potential benefits for basic research, clinical diagnosis, development of new therapeutic agents, and production of antiserum. Here, we use a substrate‐capture assay that employs a catalytically inactive mutant of thimet oligopeptidase (EC 3.4.24.15; EP24.15) to identify novel bioactive peptides in Bothrops jararacussu venom. Of the peptides captured with inactive EP24.15 and identified by mass spectrometry, three were previously identified brad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 59 publications
4
20
0
5
Order By: Relevance
“…In light of previous reports on the structure and function relationship of BPPs (50,60,90,94), our current data show that the presence of a pyroglutamic acid residue at the N-terminal position and a Pro-Pro doublet at the C terminus in BPP sequences are not enough requirements for the peptide to display BK potentiating activity.…”
Section: Protein Identifications In the Venom Of Bc Collected And Frasupporting
confidence: 48%
“…In light of previous reports on the structure and function relationship of BPPs (50,60,90,94), our current data show that the presence of a pyroglutamic acid residue at the N-terminal position and a Pro-Pro doublet at the C terminus in BPP sequences are not enough requirements for the peptide to display BK potentiating activity.…”
Section: Protein Identifications In the Venom Of Bc Collected And Frasupporting
confidence: 48%
“…The measured peptide monoisotopic mass (1384.7386) and theoretical (1384.7378) was very similar, showing a mass accuracy of 0.6 ppm, which was also observed for the identified diagnostic fragment ions (Table 1, Table 2), thus showing the high precision of the analysis. Sequence similarity showed that the peptide is homologous to other BPP described for B. moojeni venom [6] and similar to others from Bothrops neuwiedi [1,9], B. leucurus , B. erythromelas , B. alternatus [10], B. insularis [1,10,11], B. jararaca [12,13], B. jararacussu [1,10,14], B. cotiara [13], and B. fonsecai [13] (Table 3). This peptide was named as Bradykinin-potentiating peptide BAX12.…”
Section: Resultssupporting
confidence: 75%
“…Later studies confirmed that EP24.15 and EP24.16 are present in the cerebral vasculature and are capable of metabolizing BK in vivo [25,26]. Similarly, other peptidergic inhibitors of EP24.15 have demonstrated significant vasodilation effects when used in conjunction with BK, over using BK alone [29]. These findings are supportive of the work presented here, illustrating that EP24.15 and EP24.16 serve as important negative modulators of B2R activation by BK.…”
Section: Discussionmentioning
confidence: 97%